2022
DOI: 10.1123/jpah.2021-0688
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Insufficient Physical Activity Among Adults Aged 18–69 Years in India: Findings From the National Noncommunicable Disease Monitoring Survey

Abstract: Background: Sufficient physical activity (PA) significantly contributes to the prevention and control of noncommunicable diseases. This study aims to determine the prevalence of insufficient PA and associated sociodemographic and lifestyle factors among adults aged 18–69 years in India. Methods: A national population-based, cross-sectional survey was conducted during 2017–2018 among 12,000 adults that adapted globally standard data collection tools. The data were weighted and analyzed using complex samples ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
1
3
1
1
Order By: Relevance
“…Moreover, participants aged 35 to 44 demonstrated the least amount of insufficient PA, whereas those 75 years of age and older depicted the greatest levels. Consistent with previous studies, there is an inverse relationship between age and low PA, which has been identified as a significant determinant of PA [ 30 33 ]. Apparently, with increasing age, older people seem to be less motivated to be physically active and prefer quiet activities.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, participants aged 35 to 44 demonstrated the least amount of insufficient PA, whereas those 75 years of age and older depicted the greatest levels. Consistent with previous studies, there is an inverse relationship between age and low PA, which has been identified as a significant determinant of PA [ 30 33 ]. Apparently, with increasing age, older people seem to be less motivated to be physically active and prefer quiet activities.…”
Section: Discussionsupporting
confidence: 90%
“…This allowed them to perform physical activities more easily without experiencing limitations or discomfort. 27 Motivation influenced the level of physical activity. Semakin tinggi motivasi yang berasal dari diri sendiri akan meningkatkan keinginan untuk memiliki perilaku aktivitas fisik yang lebih baik.…”
Section: Discussionunclassified
“…Overweight and obesity prevalence is increasing steadily in India (Adult aged 18+ years: 2000: 11.4%, 2016:19.3%: Children and adolescent (aged 5–19 years): 2006: 3.2% 2016: 6.8%) for the past two decades (WHO, 2023b). This escalation can be attributed to shifts in dietary patterns and a decline in physical activity (Ramamoorthy, Kulothungan, & Mathur, 2022; Ramamoorthy, Leburu, Kulothungan, et al, 2022). Initiatives such as NP‐NCD, Fit India Movement, Eat Right India, school health programs, smart cities mission, promotion of yoga by government were made by the government to prevent and control the risk factors.…”
Section: Discussionmentioning
confidence: 99%